Engineering multi-dimensional evolutionary forces to combat cancer - McCoach, Caroline E. (Cancer Discov, 2019)
With advances in technology and bioinformatics we are now positioned to view and manage cancer through an evolutionary lens. This perspective is critical as our appreciation for the role of tumor heterogeneity, tumor immune compartment, and tumor micro-environment on cancer pathogenesis and evolution grows. Here, we explore recent knowledge on the evolutionary basis of cancer pathogenesis and progression, viewing tumors as multi-lineage, multi-component organisms whose growth is regulated by sub-component fitness relationships. We propose reconsidering some current tenets of the cancer management paradigm in order to take better advantage of crucial fitness relationships to improve cancer patient outcomes.